FACTORS INFLUENCING CUSTOMERS PURCHASE INTENTION IN ONLINE SHOPPING AMONG STUDENTS AT UNIVERSITI MALAYSIA KELANTAN, CITY CAMPUS - Raja Rosnah Raja Daud; Hazrina Hasbolah; Syamsuriana Sidek; Fadhilahanim Aryani Abdullah; Munirah Mahshar; Nurul Azwa Mohamed Khadri; Nurul Asyikin Abdul Qayyum, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
In Malaysia, online shopping become popular recently due to the convenience of online shopping. However, several barriers include the genuine of products sell in online, the shopping experiences includes sensory experience, less webpage user-friendly and thought-provoking become restrict determinants for public to shops online. Thus, this study is conducted to identify the factors influencing customers purchase intention in online shopping among students at Universiti Malaysia Kelantan, City Campus. 364 respondents were randomly selected through the questionnaire. The Statistical Package for Social Sciences (SPSS) version 26.0 was used to analyse the data. Descriptive analysis and correlation were applied to this study. The results showed that attitude, subjective norms, and perceived behavioral control had positive impact on intention to purchase online shopping. It is suggested that future research can be conducted in a fast -growing area and the results obtained will be more comparable and provide a direction that can reflect the impact of online purchases among students.